Synthesis of amphiphilic block copolymers - Subramanian Alamelu Suriya. (2008)
The importance of amphiphillic block copolymers is emphasized by the ability of such materials to demonstrate molecular self assembly by phase segregation due to the incompatibility between the chemically different segments. Segregation here is limited to microphase as the opposing entities are covalently bonded and thus giving rise to well defined structural morphologies of nano order. Such self assembled constructions have potential applications as templates for synthesis of other nanomaterials, over which there is poor control in size and form.